The effects of land‐use conversion on evapotranspiration and water balance of subtropical forest and managed tea plantation in Taihu Lake Basin, China. Issue 8 (16th August 2022) - Geng, Jianwei; Li, Hengpeng; Pang, Jiaping; Zhang, Wangshou; Shi, Yunjie
Abstract: Widespread clearing of natural forests for tea plantations have profoundly altered the local water balance and energy budget. However, studies of comprehensive effects of land‐use conversion on energy and hydrological cycling are still rare. In this study, we used 5 years (2014–2018) of eddy covariance (EC) data, modelled estimates, and hydrological monitoring of different functional layers (canopy, litter and soil layers) to summarize the seasonal and inter‐annual variations and differences of evapotranspiration and water balance components in tea plantations ( Camellia sinensis ) and natural bamboo forests ( Phyllostachysedulis ). Results suggested the bamboo forest had higher actual evapotranspiration (ETa ) (835 ± 5 mm) than the tea plantation (730 ± 19 mm), owing to differences in canopy conditions and plant physiology. Evident differences in ETa components were found between the tea plantation site and the bamboo forest site. The proportion of transpiration ( E tr ) was higher at the bamboo site (0.71–0.76) than the tea plantation site (0.60–0.65). Additionally, the soil evaporation ratio (0.10–0.13) was lower at the bamboo forest site than the tea plantation site (0.21–0.24) due to vegetation structure differences altering the radiation energy partitioning between the two sites. Moreover, the tea plantations were more susceptible to drought stress with low water storage in soil and simple rhizome‐root system. The comprehensive water holding capacity of canopy, litter, and soil layers of bamboo forest was 1.0–1.8 times of that in tea plantation. Compared with bamboo forest, pruning and losing of soil with intensive management activities enhanced drainage at the tea plantation site. This study provides insights into land‐use conversion of subtropical forest and managed tea plantation that have important implications on regional energy and water budgets. Abstract : The bamboo forest had higher evapotranspiration (835 ± 5 mm) than tea plantation (730 ± 19 mm), owing to differences in canopy conditions and physiology effects. The comprehensive water holding capacity of canopy, litter and soil layers of bamboo forest was 1.0–1.8 times of that in tea plantation. Pruning and soil losing with intensive management activities enhanced drainage at the tea plantation compared to bamboo forest.